(untitled) (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2024)
It is undeniable that the COVID-19 pandemic has brought about profound and significant changes in the Brazilian landscape, encompassing various aspects of society. However, the primary scope of this article focuses on analyzing the legal perspective, addressing the challenges and impacts generated by the aforementioned pandemic. Furthermore, it seeks to provide a detailed understanding of the Brazilian Multi-Door Justice system, a tool designed to ensure broad access to judicial avenues. The methodology employed in the preparation of this study was based on rigorous bibliographic research, supported by legal sources. The central focus was on mediation and conciliation, considered as alternative methods of conflict resolution, and on the impacts of the COVID-19 pandemic in the context of the Brazilian multi-door justice system.